CFLIP overexpression in T cells in thymoma‐associated myasthenia gravis. Issue 9 (22nd July 2015) - Belharazem, Djeda; Schalke, Berthold; Gold, Ralf; Nix, Wilfred; Vitacolonna, Mario; Hohenberger, Peter; Roessner, Eric; Schulze, Torsten. J.; Saruhan‐Direskeneli, Güher; Yilmaz, Vuslat; Ott, German; Ströbel, Philipp; et al.
Abstract: Objective: The capacity of thymomas to generate mature CD4+ effector T cells from immature precursors inside the tumor and export them to the blood is associated with thymoma‐associated myasthenia gravis (TAMG). Why TAMG(+) thymomas generate and export more mature CD4+ T cells than MG(−) thymomas is unknown. Methods: Unfixed thymoma tissue, thymocytes derived thereof, peripheral blood mononuclear cells (PBMCs), T‐cell subsets and B cells were analysed using qRT‐PCR and western blotting. Survival of PBMCs was measured by MTT assay. FAS‐mediated apoptosis in PBMCs was quantified by flow cytometry. NF‐ κ B in PBMCs was inhibited by the NF‐ κ B‐Inhibitor, EF24 prior to FAS‐Ligand (FASLG) treatment for apoptosis induction. Results: Expression levels of the apoptosis inhibitor cellular FLICE‐like inhibitory protein (c‐FLIP) in blood T cells and intratumorous thymocytes were higher in TAMG(+) than in MG(−) thymomas and non‐neoplastic thymic remnants. Thymocytes and PBMCs of TAMG patients showed nuclear NF‐ κ B accumulation and apoptosis resistance to FASLG stimulation that was sensitive to NF‐ κ B blockade. Thymoma removal reduced cFLIP expression in PBMCs. Interpretation: We conclude that thymomas induce cFLIP overexpression in thymocytes and their progeny, blood T cells. We suggest that the stronger cFLIP overexpression in TAMG(+) compared to MG(−) thymomas allows for the more efficient generation of mature CD4+ T cells in TAMG(+) thymomas. cFLIP overexpression in thymocytes and exported CD4+ T cells of patients with TAMG might contribute to the pathogenesis of TAMG by impairing central and peripheral T‐cell tolerance.